Numerical Assessment of Reinforced Thermoplastic Pipe (RTP) with Crack under Spanning Condition - Shu Ying, Amanda Ong (Universiti Teknologi PETRONAS, 2020)
Pipeline has proven to be an important part in the offshore oil and gas sector in transporting crude oil, natural gas or refined products. In recent years, Reinforced Thermoplastic Pipe (RTP) has gained popularity due to its high strength and high resistance to corrosion. However, the available case study or codes and standards that can be applied to this pipe was limited as it is still new to the industry. Thus, this research focuses to determine the ability of RTP to resist internal pressure under the effect cracks and spanning. The mechanical behaviour of RTP under both effects was studied through a numerical model in ANSYS Static Structural. The performance of the RTP numerical model under different crack dimension and span lengths was measured in terms of von Mises Equivalent Stress and SIF. Results were compared to ASME standard and fracture toughness of the pipe to determine its structural integrity.